2020
DOI: 10.3354/esr01057
|View full text |Cite
|
Sign up to set email alerts
|

Use of affinity analysis to guide habitat restoration and enhancement for the imperiled delta smelt

Abstract: Habitat restoration efforts in the upper San Francisco Estuary, including the Sacramento-San Joaquin Delta, California, move forward, despite a paucity of information on the environmental requirements of many targeted species. The endemic delta smelt Hypomesus transpacificus, protected under the federal Endangered Species Act, is a primary focus of those efforts despite uncertainties regarding many aspects of its relationship with the estuary’s physical and biotic resources. Here we use time-series data from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Water quality metrics from both study locations generally reflected typical winter/spring conditions (cooler temperatures, increased turbidity, decreased salinity, etc.) in the Estuary during a wet year [61] and fell within ranges consistent with Delta Smelt catches in the field [22,62]. The DWSC site, while being a long, deep channel, is effectively a dead-end slough with higher residence time and flow that is entirely driven by the tides.…”
Section: Plos Onementioning
confidence: 78%
“…Water quality metrics from both study locations generally reflected typical winter/spring conditions (cooler temperatures, increased turbidity, decreased salinity, etc.) in the Estuary during a wet year [61] and fell within ranges consistent with Delta Smelt catches in the field [22,62]. The DWSC site, while being a long, deep channel, is effectively a dead-end slough with higher residence time and flow that is entirely driven by the tides.…”
Section: Plos Onementioning
confidence: 78%
“…To offer guidance to resource managers, we previously analyzed the co-occurrence of delta smelt with several environmental factors, developing "affinity functions" that identified adequate and inadequate environmental factorcondition ranges for delta smelt (Hamilton and Murphy, 2020). Those analyses showed that the factor conditions that are suitable for delta smelt change through its life-stages and that a large portion of the upper estuary experiences habitat conditions that are seasonally unsuitable to delta smelt, and individual delta smelt frequently occupy, actually are relegated to, landscape areas that provide inadequate habitat conditions with respect to one or more essential resources at least some of the time.…”
Section: Introductionmentioning
confidence: 99%
“…Ranges of adequate conditions for four environmental factors that impact the distribution of delta smelt, drawn from occupancy studies inHamilton and Murphy (2020).…”
mentioning
confidence: 99%